2016
DOI: 10.1155/2016/1694256
|View full text |Cite
|
Sign up to set email alerts
|

Prisms to Shift Pain Away: Pathophysiological and Therapeutic Exploration of CRPS with Prism Adaptation

Abstract: Complex Regional Pain Syndrome (CRPS) is an invalidating chronic condition subsequent to peripheral lesions. There is growing consensus for a central contribution to CRPS. However, the nature of this central body representation disorder is increasingly debated. Although it has been repeatedly argued that CRPS results in motor neglect of the affected side, visual egocentric reference frame was found to be deviated toward the pain, that is, neglect of the healthy side. Accordingly, prism adaptation has been succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
79
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(97 citation statements)
references
References 47 publications
(106 reference statements)
17
79
1
Order By: Relevance
“…Reduction of pain and other CRPS symptoms following prism adaptation treatment (Bultitude & Rafal, 2010;Christophe, Chabanat, et al, 2016;Sumitani, Rossetti, et al, 2007), which is thought to increase attention to the affected side relative to the unaffected side, further supports the clinical relevance of spatial attention in CPRS. Therefore, understanding spatial biases in CRPS, and how they relate to clinical symptoms, could provide insights into the prevention and treatment of the disorder.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Reduction of pain and other CRPS symptoms following prism adaptation treatment (Bultitude & Rafal, 2010;Christophe, Chabanat, et al, 2016;Sumitani, Rossetti, et al, 2007), which is thought to increase attention to the affected side relative to the unaffected side, further supports the clinical relevance of spatial attention in CPRS. Therefore, understanding spatial biases in CRPS, and how they relate to clinical symptoms, could provide insights into the prevention and treatment of the disorder.…”
Section: Introductionmentioning
confidence: 63%
“…Furthermore, very few previous studies tested different aspects of neglect (i.e. perceptual, representational, and motor) in the same group of participants (see Christophe, Chabanat, et al, 2016;Reid et al, 2016;Sumitani et al, 2014 for exceptions).…”
Section: Introductionmentioning
confidence: 99%
“…Altered body representation and effortful movement (“neglect-like symptoms”) are predictive of worse pain outcomes in chronic CRPS six months later [85]. Treatments that target bodily and spatial representation, such as graded motor imagery [50,52,53], and prism adaptation [8,14,74] can reduce pain and other CRPS symptoms [6]. Furthermore, hand temperature asymmetries can be reduced by crossing the CRPS-affected hand into the non-affected side of peripersonal space [55].…”
Section: Introductionmentioning
confidence: 99%
“…In CRPS patients for example, distortions of the egocentric reference frame (Sumitani, Shibata, et al, 2007;Uematsu et al, 2009) and a lateralized spatial bias in tactile and visual processing (Bultitude et al, 2017;Filbrich et al, 2017;Moseley et al, 2009) have been demonstrated, as well as symptoms suggesting a distorted representation of the affected limb. Furthermore, prismatic adaptation, a therapy that is often used effectively to treat visuospatial deficits in hemispatial neglect patients, has also been shown beneficial in reducing pain and other related symptoms in CRPS (Bultitude & Rafal, 2010;Christophe et al, 2016;Jacquin-Courtois et al, 2012;Sumitani, Rossetti, et al, 2007). Alterations in space perception can also be observed in hemiplegic patients without classical symptoms of hemispatial neglect (Bartolo, Carlier, Hassaini, Martin, & Coello, 2014) or after unilateral hand amputation (Makin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Forderreuther, Sailer, & Straube, 2004;Galer, Butler, & Jensen, 1995;Galer & Jensen, 1999;Lewis, Kersten, McCabe, McPherson, & Blake, 2007;McCabe, Haigh, Halligan, & Blake, 2003;Moseley, 2004Moseley, , 2005Moseley, Gallace, & Spence, 2009;Schwoebel, Friedman, Duda, & Coslett, 2001). However, neglect-like symptomatology in CRPS could not been evidenced by classical neuropsychological testing (Christophe et al, 2016;Forderreuther et al, 2004;Kolb, Lang, Seifert, & Maihofner, 2012;Reid et al, 2016;Reinersmann et al, 2012) and visuo-spatial abnormalities have only been demonstrated in very specific experimental testing conditions. For instance, Sumitani, Shibata, et al (2007) observed difficulties in judging the position of a visual stimulus according to their own body midline in CRPS patients.…”
Section: Introductionmentioning
confidence: 99%